MEDIASI KUALITAS PELAYANAN ATAS KEMAMPUAN MANAJERIAL DAN KOMITMEN ORGANISASI TERHADAP KEPUASAN NASABAH PADA BAITUL MALL TANWIL DI LAMPUNG TIMUR - Suharto Suharto (Derivatif : Jurnal Manajemen, 2017)
This research uses managerial ability variable, organizational commitment, service quality and customer satisfaction. The purpose of this study is to determine whether there is a positive direct effect of managerial ability on service quality, knowing the positive direct effect between organizational commitment to service quality, knowing positive direct effect between managerial ability to customer satisfaction, knowing positive direct effect between organizational commitment to customer satisfaction, And know the positive direct effect of service quality on customer satisfaction.This research method is quantitative, that is research procedure which produce descriptive based on result of quantitative analysis to research variable that is managerial ability, organizational commitment, service quality and customer satisfaction. The population in this study is 1974. The sample used 95 active customers have savings. Data collection techniques used questionnaires, documentation, and interviews. Analyzer used is path analysis. While testing the instrument using the validity test and reliability test.The result of the research found that managerial ability have positive direct effect to service quality, organizational commitment have positive direct effect to service quality, organizational commitment have positive direct effect to customer satisfaction, and service quality have positive effect to customer satisfaction. Of the four research variables, organizational commitment variables have the most direct positive influence on service quality.Keywords:       Managerial ability, organizational commitment, service quality, customer satisfaction.